Diagnostico de fitonematodos en suelos de cultivos frutales - Hernandez Hernandez, R.=700 1 Del Vallin, G.; Hernandez, D.
(Es, En)
Ilus., 11 ref.
Keywords: MELOYDOGINE; ROTYLENCHUS; HELICOTYLENCHUS; PRATYLENCHUS; PSIDIUM GUAJAVA; ANANAS COMOSUS; CUBA